KESULITAN BELAJAR BAHASA JEPANG SISWA SMK NEGERI KESEHATAN DAN PARIWISATA BANGKINANG - Delfi Elvira; Nana Rahayu; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research is a quantitative descriptive study which aims to determine the difficulties learning by students of class XII Pharmacy 2 SMK Negeri Kesehatan and Pariwisata Bangkinang in learning Japanese. The population in this study were all students of class XII Pharmacy 2 which amounted to 40 students, while the sample in this study amounted to 20 students. The instrument used in this study is a questionnaire. Based on the results of the questionnaire analysys showed that students of class XII Pharmachy 2 had difficulty in reading and writing hiragana and hiragana, difficulty in writing sentence in Japanese, difficulty in asking and confirming ownership of objects, difficulty in borrowing and lending stationery in Japanese.Key Word: Learning difficulty, Japanese